(untitled) (Bangladesh Journal of Child Health, 2020)
Background: Birth defects usually present at birth and may cause morbidity and mortality in the newborn. These defects may involve any organ system of the body. Gradually the incidence is rising due to various etiologies. The objective of the study was to find out the frequency, types and etiology of birth defects. Materials & Methods: This cross-sectional study was done in a tertiary care hospital in Bangladesh. In this study, 100 neonates with birth defects were enrolled, thoroughly examined, investigated and evaluated. Then collected data were analyzed. Results: The frequency of birth defects in this study was 1.54%. The most frequent birth defect was club foot deformity i.e. 11% and the most frequently involved organ system was cardiovascular system i.e. 28%. Among the birth defects 78% were major and only 22% were minor. Among those children with birth defect mortality was 17%; 41% were referred to advanced center and 42% were improved and discharged. In some of the cases with birth defect chromosomal anomaly, congenital infection (TORCH), maternal diabetes was found as causing factor. Conclusion: The frequency of birth defects was found 1.54% and most of the birth defects were major defect. Club foot deformity was found as the most common birth defect. Bangladesh J Child Health 2020; VOL 44 (1) :8-12